PENGARUH KOMPETISI PENGADAAN PUBLIK TERHADAP BELANJA PEMERINTAH (STUDI EMPIRIS PADA PUSAT LAYANAN PENGADAAN SECARA ELEKTRONIK KEMENTERIAN KEUANGAN) - Asep Rudi; Haryanto Haryanto (Diponegoro Journal of Accounting, 2013)
This study is aimed to explore the impact of competition in public procurement on government expenditure. Using competitive bidding model adapted from previous research this study tries to analyze the effect of competition in terms of number, distance and net assets of bidders and project size on construction cost. Using data on e-tenderring process of 50 construction projects in the e-procurement unit in Ministry of Finance, linear regression analysis proves that under competitive e-tenderring process number and net assets of bidders and project size negatively effect construction cost. However, the distance of bidders has no effect on construction cost. This study also proves that those variables simultaneously effect costruction cost. This results then show that competition in public procurement negatively effects government expenditure.